Design of Medical Self-Propelled Walking Tricycle as a Post-Stroke Rehabilitation Tool - Febritasari, Rosadila; Korawan, Agus Dwi (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
Patients recovering from a stroke may not be able to use all rehabilitation equipment due to their poor muscle strength and coordination. This study proposes to design a self-propelled walking tricycle that is a non-motorized three-wheel vehicle in a delta configuration without a pedal. This study was conducted by considering the post-stroke patient needs. It was done using two analysis methods, finite element analysis, and rapid upper limb analysis, to justify the reliability of the design. The results show that the maximum stress is 38.8 MPa in the connection area of the seat tube and down tube, while the maximum deformation is 0.399 mm in the seat post. The tricycle is constructed with 153 mm of ground clearance. Therefore, patients can lift their legs and drive the tricycle by swinging their legs repeatedly, like walking. The proposed self-propelled walking tricycle can be considered as a rehabilitation tool that can train the lower extremities. It could be used for strengthening the muscles and improve body coordination for the recovery process.